Mechanism of subwavelength imaging with bilayered magnetic metamaterials: Theory and experiment - Sydoruk, O; Shamonin, M; Radkovskaya, A; Zhuromskyy, O; Shamonina, E; Trautner, R; Stevens, C; Faulkner, G; Edwards, D; Solymar, L (2007)
We present a theoretical and experimental study of a bilayered metamaterial structure for subwavelength imaging of magnetic field. The simplest version of such a structure consists of one or two linear arrays of capacitively loaded split pipe resonators. Its subwavelength physics is governed by strongly anisotropic magnetic coupling between individual resonators and by propagation of magnetoinductive waves with wavelength much shorter than the wavelength of the electromagnetic radiation in free space. It is shown that magnetoinductive waves propagating in the lateral direction are undesirable because they spread the image. Good subwavelength imaging is achieved when, due to the strong interlayer coupling, a stop band in the vicinity of the resonant frequency appears in the dispersion characteristics. The imaging properties of the single and double lens are compared and it is shown that the double lens has a superior performance. Excellent agreement is obtained between experimental and theoretical results for the magnetic field in the image plane in the operation frequency range of 30-60 MHz. It is shown that the same mechanism is responsible for image formation using bilayered planar metamaterial structures and a design of such a lens comprising two planar layers with a total of 542 elements is provided. The conclusions are not restricted to the radio frequency region because the elements can be scaled down. © 2007 American Institute of Physics.